Transfer of Training between Music and Speech: Common Processing, Attention, and Memory - Besson, Mireille; Chobert, Julie; Marie, Céline (Frontiers in Psychology, 2011)
After a brief historical perspective of the relationship between language and music, we review our work on transfer of training from music to speech that aimed at testing the general hypothesis that musicians should be more sensitive than nonmusicians to speech sounds. In light of recent results in the literature, we argue that when long-term experience in one domain influences acoustic processing in the other domain, results can be interpreted as common acoustic processing. But when long-term experience in one domain influences the building-up of abstract and specific percepts in another domain, results are taken as evidence for transfer of training effects. Moreover, we also discuss the influence of attention and working memory on transfer effects and we highlight the usefulness of the Event-Related Potentials method to disentangle the different processes that unfold in the course of music and speech perception. Finally, we give an overview of an on-going longitudinal project with children aimed at testing transfer effects from music to different levels and aspects of speech processing.